Negative Outcomes Associated with Medication in Neonates on Parenteral Nutrition Therapy - Evelin Nataly Vega Díaz; Aida Adriana Miranda Barros; Monica Alexandra Castelo Reyna; Dennys Tenelanda López; Irvin Tubon (Pediatric Reports, 2023)
Objective: In Ecuador, studies on clinical daily practice problems focused on parenteral nutrition in neonates are scarce. Therefore, this research aimed to identify negative results associated with medications (NRAM) in neonates with parenteral nutrition (PN) in a third-level hospital in Ecuador. Material and methods: An observational, prospective, descriptive study was designed in the neonatology area of a tertiary-level public hospital, where, for over four months, the medical records, PN prescriptions, and pharmacy-managed databases of 78 patients were analyzed. Drug-related problems (DRPs) as possible causes of NRAM were classified through administrative, physicochemical, and clinical validation. Results: DRPs classified as follows were found: 78.81% by physicochemical, 17.62% by clinical, and 3.57% by administrative validation. The NRAM were 72% quantitatively uncertain, 16% needed, and 11% quantitatively ineffective. Conclusion: The NRAM associated with DRPs were statistically related to prematurity condition, APGAR score, PN time, and the number of medications administered, which suggests the need to create a nutritional therapy committee at the health facility.